The Problem of Citizenship Requirements for Presidential and Vice Presidential Candidates in Indonesia: Problematika Persyaratan Kewarganegaraan Calon Presiden dan Wakil Presiden di Indonesia - Sutan Sorik; Fitra Arsil; Qurrata Ayuni (Jurnal Konstitusi, 2023)
This article examines the problematic citizenship requirements of presidential and vice presidential candidates in Indonesia. The research method used is qualitative, with normative juridical research and constitutional comparisons with fifty countries in the world that adhere to presidential government systems. The results of the study show that each country regulates the citizenship requirements of Presidential and Vice-Presidential Candidates in its constitution. The regulation of the citizenship requirements for the candidates for President and Vice President in Constitution of the Republic of Indonesia is ideal because it is not discriminatory and also does not have multiple interpretations. Based on a comparison with fifty countries, the regulation of citizenship requirements in Indonesia falls into the first category, namely citizen/nasionality by birth/born. The challenge for Indonesia in the future is how to implement these constitutional provisions without being politicized, especially when the Presidential and Vice-Presidential Elections will be held.